Assessment of pulsating torque mitigation control strategy through tidal turbine emulation. Issue 18 (21st June 2019) - Sousounis, Marios Charilaos; Shek, Jonathan K.H.
Abstract : This article presents the modelling and assessment of a pulsating torque mitigation control strategy by using a tidal turbine emulator in a laboratory environment. Sudden changes and variability of the tidal flow velocity have the effect of creating pulsations on tidal current turbines. These pulsations have an adverse effect on tidal turbine fatigue and ultimate loading as well as the operation of the drivetrain. For the above reasons, a pulsating torque mitigation control strategy has been developed and tested which is based on modifying the reference maximum power point speed of the generator. This article presents the assessment of this pulsating torque mitigation control strategy in a laboratory setup. A 7 kW tidal current turbine is modelled in MATLAB/Simulink. The tidal turbine is emulated in the laboratory setup by using a torque‐controlled induction motor. Results show the effectiveness of the method in a laboratory environment, the ability of the generator to accelerate and decelerate based on the speed controller commands and the difference between the pulsating torque mitigation control strategy and maximum power point operation (MPPO). In addition, the experimental results are compared with a Simulink model which will show the accuracy of the modelling process.